Risk of fracture after bariatric surgery in the United Kingdom: population based, retrospective cohort study - Lalmohamed, Arief (BMJ Publishing Group Ltd., 2012)
Objectives To estimate fracture risk in patients receiving bariatric surgery versus matched controls. Design Population based, retrospective cohort study. Setting Use of records from the United Kingdom General Practice Research Database, now known as the Clinical Practice Research Datalink (from January 1987 to December 2010). Participants Patients with a body mass index of at least 30, with a record of bariatric surgery (n=2079), and matched controls without a record (n=10 442). Each bariatric surgery patient was matched to up to six controls by age, sex, practice, year, and body mass index. Patients were followed from the date of bariatric surgery for the occurrence of any fracture. We used time dependent Cox regression to calculate relative rates of fracture, adjusted for disease and previous drug treatment, and time-interaction terms to evaluate fracture timing patterns. Main outcome measure Relative rates of any, osteoporotic, and non-osteoporotic fractures. Results Mean follow-up time was 2.2 years. Overall, there was no significantly increased risk of fracture in patients who underwent bariatric surgery, compared with controls (8.8 v 8.2 per 1000 person years; adjusted relative risk 0.89, 95% confidence interval 0.60 to 1.33). Bariatric surgery also did not affect risk of osteoporotic and non-osteoporotic fractures. However, we saw a trend towards an increased fracture risk after three to five years following surgery, as well as in patients who had a greater decrease in body mass index after surgery, but this was not significant. Conclusion Bariatric surgery does not have a significant effect on the risk of fracture. For the first few years after surgery, these results are reassuring for patients undergoing such operations, but do not exclude a more protracted adverse influence on skeletal health in the longer term.